THE INFLUENCE OF COMPENSATION, WORK ENVIRONMENT AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. BANK SUMUT BRANCH OF SIPIROK - Yizreel Firman Agus; Nicholas Marpaung (Transpublika Publisher, 2023)
This study aims to determine how compensation, work environment, and work discipline influence employee performance at PT. Bank Sumut in Sipirok Branch Office. This research uses quantitative research methods with an associative approach. The population in this study were employees of PT. Bank Sumut in Sipirok Branch Office which has a total of 20 people. Sample collection technique with census sampling model / total sampling, the number of samples was 20 respondents. Data collection method questionnaire method measured using a likert scale. The analytical methods used in this study are instrument test, classical assumption test, multiple linear regression analysis and hypothesis test using SPSS. The results showed that the compensation variable had a positive and significant effect on employee performance as evidenced by tstatistic of 3,606 > 1,74588 with a significance level of 0,000 < 0,05. The work environment has a positive effect on employee performance as evidenced by tstatistic of 4.029 > 1.74588 with a significance level of 0,001 < 0,05. Work discipline has a positive and significant effect as evidenced by a fstatistic value of 4,416 > 1,74588 with a significance level of 0,000 < 0,05. Compensation, work environment, and work discipline together have a positive and significant effect on employee performance as evidenced by the results of the simultaneous significance test Fstatistic of 40,477 > Ftable 3,239. In the calculation of the coefficient of determination, a result of 0,884 was obtained, which means that the independent variable affects the dependent variable by 88,4%. The remaining 11,6% was explained by other unknown variables in the study.